Adapting the FTT-CAN Master for Multiple-bus Operation - Silva, Valter
The controller area network is still widely used as an embedded network in safety critical applications, e.g. in the automotive domain. However, requirements have changed and dependability and bandwidth limitations led to the emergence of alternative networks such as FlexRay. Nevertheless there is still room to improve CAN to try to fulfill current requirements. FTT-CAN supports multiple buses both to provide bus media redundancy and to increase the available bandwidth. The architecture and flexibility of FTT based systems enables a tight yet flexible control of redundancy and bandwidth usage without a substantial increase on the complexity of the nodes. This paper deals with the required adaptions on the FTT-CAN master node to make it capable of handling multiple buses and presents some results derived from experimental measurements made on a reference implementation.